2021
DOI: 10.3389/fneur.2021.661302
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Vestibular Function in Pediatric Cochlear Implant Recipients

Abstract: Background: Vestibular dysfunction is a complication of cochlear implantation (CI). Reports on the evaluation of vestibular function before and after CI are limited, especially in children. We investigated the effect of CI on vestibular function in pediatric patients.Patients and Methods: We routinely evaluated vestibular function before but not immediately after CI. Therefore, patients who underwent sequential bilateral CI were enrolled in this study. Seventy-three children who underwent sequential CI from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…A combined multi‐disciplinary clinic such as a post‐concussion clinic may contribute to a higher number of BPPV cases in children 14 . Although not found in any patients in this review, BPPV secondary to cochlear implant was reported by several authors, 6,26,27 which is postulated to occur due to (1) introduction of the bone dust into the labyrinth, 26 (2) otoconia that dislodged from the vibration caused by the drilling during the surgery or trauma, 6 (3) labyrinthitis 28 or (4) hydropic changes from the electrode placement in the cochlea which disturbs the endolymph flow 29 …”
Section: Discussionmentioning
confidence: 80%
“…A combined multi‐disciplinary clinic such as a post‐concussion clinic may contribute to a higher number of BPPV cases in children 14 . Although not found in any patients in this review, BPPV secondary to cochlear implant was reported by several authors, 6,26,27 which is postulated to occur due to (1) introduction of the bone dust into the labyrinth, 26 (2) otoconia that dislodged from the vibration caused by the drilling during the surgery or trauma, 6 (3) labyrinthitis 28 or (4) hydropic changes from the electrode placement in the cochlea which disturbs the endolymph flow 29 …”
Section: Discussionmentioning
confidence: 80%
“…After reviewing the research references, five additional studies were identified. Thus, 20 studies were finally selected for the meta-analysis ( 7 , 15 , 26 43 ) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we calculated the RR to directly compare the differences in vestibular function damage between the two surgical methods. Compared with cochleostomy, Koyama et al ( 7 ) and Cozma et al ( 33 ) reported that the risk of vestibular loss was reduced by 47 and 16%, respectively, when performing RW. Nevertheless, no significant difference was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vestibular function in children is sparsely reported. Koyama et al (2021) showed that minimally invasive surgery in children using the RW approach or an extended RW approach with straight electrodes is desirable to preserve vestibular function after CI. West et al (2021) describe that the vestibular function in individuals with Pendred appears to be normal (as estimated by video head impulse test), but the saccular function is abnormally sensitive, as documented by low cervical vestibular evoked myogenic potential thresholds and high amplitudes, which agrees with a "third window" effect secondary to the large vestibular aqueduct.…”
Section: Discussionmentioning
confidence: 99%